VD_FINDINFO AA 6/23 - 140/2023 vom 18. Dezember 2023 - VD Tribunal cantonal (2023)
CONFLIT DE COMPÉTENCES, TRAVAILLEUR, NOTION, REJET DE LA DEMANDE, ACCIDENT, SUITE D'UN ACCIDENT | 1a LAA, 78a LAA, 15 LAI